2001
DOI: 10.1083/jcb.152.4.693
|View full text |Cite
|
Sign up to set email alerts
|

Stromelysin-1 Regulates Adipogenesis during Mammary Gland Involution

Abstract: The matrix metalloproteinase MMP-3/stromelysin-1 (Str1) is highly expressed during mammary gland involution induced by weaning. During involution, programmed cell death of the secretory epithelium takes place concomitant with the repopulation of the mammary fat pad with adipocytes. In this study, we have used a genetic approach to determine the role of Str1 during mammary involution. Although Str1 has been shown to induce unscheduled apoptosis when expressed ectopically during late pregnancy (Alexander, C.M., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
181
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(197 citation statements)
references
References 71 publications
10
181
2
2
Order By: Relevance
“…Interestingly, treatment of 3T3-F442A preadipocytes with synthetic MMP inhibitors and by neutralizing antibodies decreased differentiation, suggesting that MMP activities were required for adipocyte conversion (12). In contrast, another study showed that addition of TIMP-1 or MMP inhibitor GM6001 accelerated 3T3-L1 adipocyte differentiation (14). In addition, this study also demonstrated that stromelysin-1 (MMP-3) determined the rate of adipose reconstitution during mammary gland involution in mice (14).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Interestingly, treatment of 3T3-F442A preadipocytes with synthetic MMP inhibitors and by neutralizing antibodies decreased differentiation, suggesting that MMP activities were required for adipocyte conversion (12). In contrast, another study showed that addition of TIMP-1 or MMP inhibitor GM6001 accelerated 3T3-L1 adipocyte differentiation (14). In addition, this study also demonstrated that stromelysin-1 (MMP-3) determined the rate of adipose reconstitution during mammary gland involution in mice (14).…”
mentioning
confidence: 74%
“…In contrast, another study showed that addition of TIMP-1 or MMP inhibitor GM6001 accelerated 3T3-L1 adipocyte differentiation (14). In addition, this study also demonstrated that stromelysin-1 (MMP-3) determined the rate of adipose reconstitution during mammary gland involution in mice (14). Moreover, on a high fat diet, stromelysin-3 (MMP-11)-deficient mice developed adipocyte hypertrophy compared with wild-type mice (15).…”
mentioning
confidence: 96%
“…For example, Maquoi et al (18) demonstrated that MMP3 Ϫ/Ϫ mice had increased adipocyte hypertrophy when fed a high-fat diet, and Alexander et al (17) showed that MMP3 Ϫ/Ϫ (Str1 Ϫ/Ϫ ) mice had accelerated adipocyte differentiation during mammary gland involution. In the same study, Alexander et al noted that MMP3 Ϫ/Ϫ mice backcrossed onto another background (FVB/N) became obese with age (17). In contrast to our study, both Maquoi et al (5), in an earlier study, and Chavey et al (4) found that MMP3 expression levels were upregulated in adipose tissue isolated from obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…• Adipocyte maturation requires the replacement of the surrounding interstitial matrix with a basement membrane 148,149 *Reviewed in REFS [121][122][123][124] .…”
Section: Differentiationmentioning
confidence: 99%